Pengaruh Thin capitalization, Ukuran Perusahaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Salma Nurhaliza Putri; Enny Susilowati Mardjono; Ngurah Pandji Mertha Agung Durya; Purwantoro (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Firm value reflects investors' assessment of its achievements and performance. This research aims to investigate the impact of factors such as firm size, dividend policy, and thin capitalization on firm value. Using secondary data from 188 food & beverage industries listed on the Indonesia Stock Exchange between 2020 and 2022, this analysis focused on a sample of 72 companies. This analysis uses multiple linear regression analysis methods and classical assumption testing which includes normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and hypothesis testing consisting of f test, t test, and r test. This study states that firm size, dividend policy, and thin capitalization all have an impact on firm value. Which can be concluded that the regression model developed complies with classical assumptions so that the data can be used. Overall, firm value is strongly influenced by its dividend policy, size, and thin capitalization. Based on the research, suggestions that can be given should include more moderator or intervening variables to support the hypothesis.